Asymptotic Stability Analysis of Binary Heterogeneous Traffic Based on Car-Following Model - Hao Wang; Qian Wan; Wei Wang (Discrete Dynamics in Nature and Society)
We study the asymptotic stability of Chandler Model for a heterogeneous traffic by using numerical simulations. A simple binary platoon is considered which consists of two types of vehicles. Platoon stabilities under various kinds of combinations of parameters are investigated. It is found that the stability of the binary platoon cannot be determined by the mean values of individual vehicle’s parameters. Some combinations of parameters that benefit to the platoon stability are found. Several interesting properties of binary platoon’s stability are summarized. The analytic stability criterion of heterogeneous traffic reported in the historical literature is studied. The result indicates the analytic criterion is not rigorous, which is apt to overestimate the stability of heterogeneous platoon.